Prevention and treatment of venous thromboembolism in pregnancy in patients with hereditary antithrombin deficiency - James AH; Konkle BA; Bauer KA (Dove Medical Press, 2013)
Andra H James,1 Barbara A Konkle,2,3 Kenneth A Bauer4 1Department of Obstetrics and Gynecology, University of Virginia, Charlottesville, Virginia, 2Puget Sound Blood Center, Seattle, Washington, 3Department of Medicine, University of Washington, Seattle, Washington, 4Department of Medicine, Beth Israel Deaconess Medical Center and VA Boston Healthcare System, Harvard Medical School, Boston, Massachusetts, USA Objective: The aims of the study reported here were to provide data from six pregnant subjects who were enrolled in a clinical trial of antithrombin (AT) concentrate, discuss other published case series and case reports, and provide general guidance for the use of AT concentrate for inherited AT deficiency in pregnancy. Methods: In the late 1980s, 31 AT-deficient subjects were enrolled in a prospective treatment trial of the plasma-derived AT concentrate Thrombate III®. Herein, newly available treatment data about the six pregnant subjects in the trial is tabulated and summarized. Results: All six experienced venous thromboembolism (VTE) during pregnancy, were dosed according to a weight-based protocol, and were treated concomitantly with anticoagulation. Loading doses of AT concentrate of 54–62 units/kg were followed by maintenance doses of 50%–100% of the loading dose for 3–10 days. At the time of labor, loading doses of 46–50 units/kg were followed by maintenance doses of 50%–75% of the loading dose for 5–7 days. None of the six experienced recurrent thrombosis while receiving treatment with AT concentrate. Conclusion: Currently we suggest that women with AT deficiency who are pregnant or postpartum and have a personal history of VTE or current VTE receive AT concentrates. Keywords: thrombophilia, thrombosis, plasma-derived concentrate, labor, delivery, heparin.